Activity quantification and dosimetry in radiopharmaceutical therapy with reference to 177Lutetium - Ramonaheng, Keamogetswe; Qebetu, Milani; Ndlovu, Honest; Swanepoel, Cecile; Smith, Liani; Mdanda, Sipho; Mdlophane, Amanda; Sathekge, Mike (Frontiers in Nuclear Medicine, 2024)
Radiopharmaceutical therapy has been widely adopted owing primarily to the development of novel radiopharmaceuticals. To fully utilize the potential of these RPTs in the era of precision medicine, therapy must be optimized to the patient's tumor characteristics. The vastly disparate dosimetry methodologies need to be harmonized as the first step towards this. Multiple factors play a crucial role in the shift from empirical activity administration to patient-specific dosimetry-based administrations from RPT. Factors such as variable responses seen in patients with presumably similar clinical characteristics underscore the need to standardize and validate dosimetry calculations. These efforts combined with ongoing initiatives to streamline the dosimetry process facilitate the implementation of radiomolecular precision oncology. However, various challenges hinder the widespread adoption of personalized dosimetry-based activity administration, particularly when compared to the more convenient and resource-efficient approach of empiric activity administration. This review outlines the fundamental principles, procedures, and methodologies related to image activity quantification and dosimetry with a specific focus on 177Lutetium-based radiopharmaceuticals.